Factors Motivating Domestic Tourists to Visit Destinations within Cambodia During the Green Season - Veasna Ung; Younes Mohammat; Kunthea Phoeuk; Sokhom Neng (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study investigates the primary push (socio-psychological) and pull (destination-based) factors influencing Cambodian domestic tourists' intentions to travel during the "Green Season". Despite the government's strategic promotion of this period, academic research on the specific motivations of local travelers remains scarce. A qualitative phenomenological research design was employed, involving in-depth interviews with 27 participants, including domestic travelers, tourism business owners, and employees of the Ministry of Tourism. Data were gathered through purposive non-probability sampling and analyzed using thematic analysis. The findings reveal that primary push factors include the need for stress reduction, mental restoration, and social bonding with family and friends, and pull factors are driven by the aesthetic appeal of lush landscapes and waterfalls, coupled with economic incentives such as lower accommodation and food costs. The results suggest that the green season is perceived as a "value season" that fulfills both psychological and social needs through digital sharing. This research provides evidence-based recommendations for stakeholders to enhance year-round tourism sustainability in Cambodia.